BRIDGES OF COMFORT: NURSE-LED INTERVENTIONS IN FEEDING AND MOTHERHOOD - SHANMUGAPRIYA SHANMUGASUNDHARAM; SHANKAR SHANMUGAM RAJENDRAN; KANNAN KASINATHAN; ASHALIN RAJA BRINTHA PALAS; NEEVATHA PALANI; ABISHA MARY ANTONY JOHNSON KENNADY; DR. WINSTON THOMAS (The Bioscan, 2025)
Background: Feeding difficulties are more common in children with cerebral palsy and have an effect on growth, Nutritional state, general health, social interaction and behavior and developmental outcomes. Feeding practices and effective care for children with cerebral palsy are essential to avoid complication and reduce stress for the caregiver and the child. Nurse-led interventions, including education on positioning, Modified food texture, Modified feeding strategy and Swallowing exercises for managing these health risks and improving quality of life of the mothers and the children with cerebral palsy. Objectives: Assess the effectiveness of Nurse led intervention on feeding practices and explore the feeding experiences among mothers of children with Cerebral palsy. Materials and Methods: A mixed-method explanatory sequential design was utilized based on Health Belief Model. A total of 50 mothers of children with cerebral palsy were included in the study. Quantitative data were gathered through a validated Feeding/Swallowing Impact Survey Tool before and after nurse-led interventions, while qualitative insights were obtained through phenomenological interviews with five mothers. Statistical analyses and thematic analysis were conducted. Result: In the pretest, the feeding practices lies in the very high to high impact score. Following intervention, the Post test findings showed a significant reduction in mean feeding practices impact (from 75.53 to 42.31). Qualitative Thematic analysis revealed Feeding as an Emotional and Physical challenge, Impact on Family Dynamics, Adaptive Strategies and Resilience, Support System and Hospital experiences, including of 13 subthemes. Conclusion: Nurse-led interventions significantly improved feeding practices and reduced fear and anxiety and complications during feeding among mothers of children with cerebral palsy. Addressing physical challenges and enhancing family involvement, support services and accessible care services are crucial for betterment of quality of life of children and improving feeding practices among mothers.